Application of colored timed Petri nets for cement production simulation - Irina A. Sedykh; Eugeny S. Anikeev (Advanced Engineering Research, 2016)
The work objective is to develop a special model of the complex distributed object - the cement production - on the basis of the colored timed Petri nets including its analysis and estimation of effectiveness and correctness. Various kinds of the Petri nets together with the methods of their determination and performance dynamics are considered. An operation algorithm is formulated in the matrix form for the colored timed Petri nets. On the basis of the colored timed nets, a mathematical model that allows predicting the cement production volume for a defined period is built. The discussed model is realized in the C++ language. The simulation results are compared to the factual data. It is found that the implemented model with a reasonable degree of accuracy predicts the output volume of the cement production. The developed methods are operable and applicable in the manufacturing process simulation as part of an automated control system of the technology parameters.